Brands of Zen: Kitō jiin in Contemporary Japanese Sōtō Zen Buddhism - Graf, Tim (2017)
This dissertation examines contemporary Japanese prayer monasteries (kitō jiin) as sites of religious branding and priestly training. It also explores ways Sōtō Zen prayer monasteries shed light on the broader topic of interplay between training and branding in the making of this-worldly benefits (genze riyaku).
Keywords: Hochschulschrift